GC-MS analysis of ethanol extract of Wattakaka volubilis (l.f.) stapf. lea - A. Maruthupandian,; V.R. Mohan, (International Journal of Phytomedicine, 2011)
Wattakaka volubilis (L.f) Stapf known to the Palliyars as “Kurinjan” is an important medicinal plant. The Palliyar tribe, inhabitants of Sirumalai hills, Western Ghats, Tamil Nadu. India, use this plant as antidiabetic. The present investigation deals with GC-MS analysis of ethnol extract of the above said plant. Fifteen compounds were identified.